Does money matter in the IS curve? The case of the UK - Barry E. Jones; Livio Stracca (European Central Bank (ECB), 2008)
Narrow and broad money measures (including Divisia aggregates) have been found to have explanatory power for UK output in backward-looking specifications of the IS curve. In this paper, we explore whether or not real balances enter into a forward-looking IS curve for the UK, building on the theoretical framework of Ireland (2004). To do this, we test for additive separability between consumption and money over a sizeable part of the post-ERM period using non-parametric methods. If consumption and money are not additively separable, then real money balances enter into the forward-looking IS curve (the converse does not hold, however). A main finding is that the UK data seem to be broadly consistent with additive separability for the the more recent period from 1999 to 2007.
Keywords: C14; C43; C63; E21; E41; 330; Additive Separability; Divisia Monetary Aggregates; IS Curve; measurement error; Non-Parametric Tests; IS-LM-Modell; Geldmenge; Privater Konsum; Nichtparametrisches Verfahren; Statistischer Fehler; Großbritannien